DETERMINATION OF SOME DOMESTIC RADIATORS' THERMAL CAPACITY NUMERICALLY - Dalkilic, A. S.; Acikgoz, O.; Ekici, E.; Wongwises, S. (YILDIZ TECHNICAL UNIV, 2019)
Free convection and radiation comprise the heat transfer mechanisms through which a hydronic household radiator conveys heat from its surface to air and surrounding surfaces. It should also be noted that their performance could be enhanced by improving surface geometries as well as increasing temperature levels. In the present study, heat transfer rates and convective heat transfer coefficients occurring through the investigated radiators, were numerically examined. To this end, radiators at two different dimensions having two different geometric shapes were drawn and analyzed in the program Ansys 17. The heat transfer rates obtained from the program were validated via radiator producer catalogues. Furthermore, the influence of parameters, such as water velocity in the radiators and thus mass flow rate, temperature difference between water inlet and outlet and also between radiator surface and surrounding air on convective heat transfer coefficient over radiator, were scrutinized.
Keywords: Radiator; Heat Transfer; Natural Convection; Radiation; ANSYS; HEAT-TRANSFER COEFFICIENT; FLOW; COMFORT; Thermodynamics